Sistem Pengumpulan Dana Wakaf Tunai Melalui Transaksi Layanan Digital Di Indonesia - Muhammad Amin; Iman Sidik Nusannas (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This study aims to explore the cash waqf fundraising system conducted through digital transaction services in Indonesia. This study uses a systematic literatur review. The results of this study indicate that the realization of cash waqf fundraising is still relatively small, at 1,8% compared to the cash waqf target set by the Indonesian Waqf Board. Factors causing the low realization of waqf fundraising are the relatively low public literacy about waqf, weak management and development of waqf by nazir in a modern way, and the majority of waqf asset management in Indonesia is allocated for social purposes. The cash waqf fundraising system through digital transaction services is very helpful in increasing cash waqf participation from the public.